THE ART OF VIRTUAL LEADERSHIP : INSIGHTS FROM A LITERATURE REVIEW - Pringgabayu, Dematria; Waruwu, Fotuho; Sobandi, A; Disman, Disman (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
As the world becomes increasingly digital, virtual leadership is becoming more and more prevalent. The ability to lead teams and organizations from a remote location is a skill that is in high demand. But what does it take to be a successful virtual leader? A recent systematic literature review delves into the art of virtual leadership and reveals some key insights. In this review, researchers analyzed various studies on virtual leadership and identified common themes and best practices. From communication strategies to technology tools, the review provides a comprehensive guide for those looking to lead teams in a virtual environment. Whether you're a seasoned virtual leader or just starting to navigate the world of remote work, the insights from this review are sure to be valuable. So, let's dive in and explore the art of virtual leadership together